Rocky Gerung Critical Language Analysis in Indonesia Lawyers Club (ILC) at Tv One - Ratih Safitri; Wayan Satria Jaya; Supriyono Supriyono; Eny Dwi Marcela (IJLHE: International Journal of Language, Humanities, and Education, 2020)
This research was conducted for several purposes, namely (1) to find out and describe the critical language form of Rocky Gerung, (2) to know and describe its motives and objectives, (3) to know and describe the critical message conveyed by Rocky Gerung in the Indonesia Lawyers Club on tvOne. Research methods use content analysis. The data and data source of this research is the critical language of Rocky gerung which aired on ILC tvOne. Collection by uploading ILC impressions on youtube specifically on the presence of Rocky Gerung and transcribe conversations into data sheets. The results showed that Rocky Gerung's critical language in the ILC aired on tvOne was generally firm, straightforward, and clear. The firmness of the RG language is because it is directly in the ILC discussion forum entitled 'Testing KPU Neutrality', 'The Face of Our Decomrasiration', and FPI Permit Back and Forth'. The goal is to criticize government policies, regulations, including the KPU and the constitutional court. The message conveyed, namely the government needs to be wise and fair to see and respond to every conflict that arises from the bottom to the top of the political elite so as to create a comprehensive justice.